Winthropos : Poems - Kalogeris, George (Book collections on Project MUSE., 2021)
""Winthropos," the title of George Kalogeris's new collection of poetry, comes from the "Greek-ified" name his father, an immigrant from Greece, gave to the blue-collar New England town where the family lived. Following in the spirit of his acclaimed Guide to Greece, Kalogeris conjures the town of Winthrop, Massachusetts, as a central locus of lyric and elegiac memory. While the poems often reach back into the Hellenic past for imagery and inspiration, they just as often reside in the American present of their conception. The author's grocer-father worries over his son possibly being drafted for Vietnam, standing at his butcher's block like a priest in Homer trying to read the gory entrails. Andy Williams singing "Moon River" in the family parlor evokes the River Lethe flowing halfway up a straw as a beloved Uncle Charlie lies dying in hospice. Speech class lessons with "Mrs. Sea Gull" (Mrs. Segal) reveal English diphthongs that are hard to pronounce, but "Thalassa" rolls off the speaker's tongue like pebbles on Winthrop Beach. Rich with classical allusion and tragic vision, including translations of Cavafy and Leopardi, "Winthropos" plumbs childhood memory and local custom in a work of meditative power and evocative beauty"--